Islam as Bonding Social Capital - Madjid, St. Salehah (PILAR, 2023)
This study aims to identify which religion Islam as social capital binds to traders in the face of the covid 19 pandemic. The study was conducted on Muslim street vendors in Losari Beach, Makassar. The study used descriptive research with qualitative data collection methods. The results of the study state that religion can be a bonding social capital for traders. This is proven by Muslim street vendors in Makassar with the characteristics of attachment, exclusive network, strong reciprocal relationships, strong Muslim identity, group solidarity, belief in norms and strong values.